Effect of dietary inclusions of different types of Acacia mearnsii on milk performance and nutrient intake of dairy cows - Lindokuhle C. Mhlongo; Piers Kenyon; Ignatius V. Nsahlai (Veterinary and Animal Science, 2023)
This study investigated the effects of including different types of Acacia mearnsii (tannin extract and forage) on nutrient intake and milk performance in dairy cattle. Holstein-Friesian x Jersey dairy cows (n per Experiment = 24) that had 200 days in milk were selected for this study in a completely randomized study design. This study was conducted under on-farm conditions at Springfontein dairy farm, a farm that lacked a functional bodyweight scale to measure the cow bodyweight and a computer system to register cow parity. Cows were assigned Acacia mearnsii tannin extract (ATE) pellets which were added with 0 (0ATE), 0.75 (0.75ATE), 1.5 (1.5ATE) or 3 (3ATE) % ATE in pellets while 0ATE was a commercial protein concentrate (Experiment 1). Cows were assigned Acacia mearnsii forage (AMF) at a rate of 0 (0AMF), 5 (5AMF), 15 (15AMF) or 25 (25AMF) % AMF inclusion in corn silage-based diet (Experiment 2). For both Experiments, treatments had six cows each, in which they were adapted (14 d) to diets before data collection (21 d). All AMF inclusions decreased (P<0.0001) dry matter intake (DMI), crude protein intake (CPI), neutral detergent fibre intake (NDFI), acid detergent fibre intake (ADFI) and organic matter intake (OMI) at 25AMF. Linear (P<0.0001) and quadratic (P<0.001) effects were observed on DMI, CPI, NDFI, ADFI and OMI. Inclusions of AMF in corn silage diets affected milk yield, protein yield, lactose yield and milk protein percentage (P<0.001). Linear effect was present in milk yield per DMI (P<0.0001). In conclusion, the dairy cow diet supplemented with ATE pellets did not have a beneficial effect on the nutrient intakes and milk yield. However, the AMF supplemented in corn silage of the dairy cow diet, increased milk production due to positive effects on nutrient intake, which was favourably influenced from a nutritional point of view.